Ground Zero: A bibliometric analysis of L2 vocabulary research 1986-1990 - Paul Meara (LingBaW)
This paper uses a co-citation analysis to examine the research on vocabulary acquisition that was published in 1990. Two analyses are presented. The first is a detailed account of the 1990 research on its own terms. The second analysis places this work in a larger context by looking at research published in a five-year window covering 1986-1990.